2021
DOI: 10.3390/nu14010073
|View full text |Cite
|
Sign up to set email alerts
|

Association of Macronutrients Composition, Physical Activity and Serum Androgen Concentration in Young Women with Polycystic Ovary Syndrome

Abstract: The roles of dietary macronutrients and physical activity (PA) in patients with PCOS have not been sufficiently reported, especially in adolescent girls. To address this knowledge gap, we evaluated the associations between serum concentrations of total testosterone (tT), free testosterone (fT), androstenedione (A), dehydroepiandrosterone-sulfate (DHEA-S), sex hormone-binding globulin (SHBG) and dietary macronutrients intake as well as different types and levels of PA. The study population consisted of 96 girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
(94 reference statements)
0
6
0
Order By: Relevance
“…This is important because our previous research showed certain correlations between macronutrients in the diet and the tested androgens in the PCOS and/or control group. In the girls studied, we revealed a positive correlation between the serum concentration of androstenedione and the supply of total fats and MUFA, as well as a negative correlation between the above-mentioned androgen, and the supply of total protein, vegetable protein, and fibre 40 . Intervention studies by other authors showed a beneficial effect of dietary interventions on insulin resistance in PCOS patients and the normalization of hyperandrogenemia 55 .…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…This is important because our previous research showed certain correlations between macronutrients in the diet and the tested androgens in the PCOS and/or control group. In the girls studied, we revealed a positive correlation between the serum concentration of androstenedione and the supply of total fats and MUFA, as well as a negative correlation between the above-mentioned androgen, and the supply of total protein, vegetable protein, and fibre 40 . Intervention studies by other authors showed a beneficial effect of dietary interventions on insulin resistance in PCOS patients and the normalization of hyperandrogenemia 55 .…”
Section: Discussionmentioning
confidence: 78%
“…Unfortunately, in contrast to these findings, our previous studies did not show any significant correlations between fibre intake and androgen levels in girls with PCOS. However, the entire study cohort showed a negative correlation between fibre intake and testosterone and androstenedione concentrations 40 .…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations